AB0468 AGE RELATED DIFFERENCES IN PATIENTS WITH GIANT CELL ARTERITIS. (2nd June 2020) - Dieguez Pena, P.; Gimena Reyes, B.; Maure Noia, B.; Argibay, A.; Vázquez Triñanes, C.; Rivera Gallego, A. J.; Sousa Dominguez, A.; Estevez, M.
Abstract : Background: Few data are available on the epidemiology and management of giant cell arteritis (GCA) in patients over 75 years despite the progressive aging in our societies. In other diseases this subgroup of patients presents important differences in the management and prognosis of their pathologies. Objectives: To explore this situation by comparing two subgroups of patients, older and younger than 75, assesing possible changes in demographic characteristics, diagnostic tests, treatment and outcome. Methods: We perform a retrospective review of charts, laboratory data, image studies, treatment and outcome of biopsy-proven GCA in our institution (Complejo Hospitalario Universitario de Vigo) between 1 January 2000 and 30 November 2019. Results: During study period 124 patients were analysed, 51 in the subgroup of <75 (mean age 64.6 (56-75)) and 73 in the subgroup of >75 (mean age 81.8 (76-89)). There were no differences about sex (female 76.6% vs. 65%) or in the Charlson index between the two groups (0-1 in 72% of patients). Older patients present more frequently with headache (49.2 % vs 32.3%), polymyalgia rheumatica (53.4 % vs 45.1%), weight loss (48% vs 39.2%) and ischaemic manifestations (72.6 % vs 51%), including visual disturbances (26% vs 11.8%). Younger patients present more frequently with fever (33.3% vs 19.2%). Median ESR was similar: 98 vs 96 mm/h; median CPR was slightly higher in younger patients 94.5 mg/dL vs 71.59 mg/dL. PET-TC was performed more frequently at diagnosis in the subgroup of younger patients (29.4% vs 12.3%) and during follow-up period in the other subgroup (3.4% vs 7%) with evidence of involvement of large vessels in 14 of them. Initial treatment consisted of corticosteroids in 100% of patients with the most frequent doses, in both groups, between 40-60 mg/day of prednisone or equivalent. The subgroup of < 75 were treated more aggressively receiving pulses of methylprednisolone (125-250 mg) 12 patients (23.5%), while in the subgroup >75 lower doses were started more frequently (<40mg/day in 21 patients, 28.7%). Lowering corticosteroids to <5 mg/day were slower in the subgroup of patients <75 (47.1% within the first 12 months) with respect to the >75 (58%). During the follow-up period 47 patients had at least one relapse, we did not observe statistical differences between both groups (21 patients <75 and 26 patients >75). Time to first relapse was more frequent within the first year of treatment (12 and 16 patients respectively). We could not identified any factor related to relapses in our multivariate analysis. There was no significant differences between both groups about starting MTX (33.3% and 38%) on relapses. Only two patients started TCZ (one in each group). Twenty-nine patients died during follow-up period (11.7% in <75 vs. 31.5% in >75), but none were related with GCA. Conclusion: 1. No differences were observed in sex, comorbidities (including cardiovascular risk factors) or laboratory markers between both groups. 2. Younger patients presented with less frequent ischaemic symptoms; however we perform a more powerful treatment, both in doses and duration. Disclosure of Interests: None declared